Main geological features and lithotectonic description of rocks of the potassium horizon IV within the Starobin deposit - Petrova, Natalia S.; Denisova, Natalia Yu.; Kirykovich, Aliaksei V. (Journal of the Belarusian State University. Geography and Geology, 2019)
The article is devoted to potash horizon IV. It’s one of the most developed horizons in the cross-section of the Mid-Upper-Famennian saliferous formation within the Pripyat potash-bearing basin. Horizon distributional pattern, main features of the cross-section are considered with geological variability assessment within the mine fields of the JSC «Belaruskali».   The connection between the structural plan and the block structure of the subsalt bed is reflected. The authors provide data on the structural and substantial characteristics of the potash ore, rock salt and halopelites of the preferred mining layer. The basis for preparation and writing of the text was author’s materials obtained as a result of geological exploration works and scientific investigations.
Keywords: Pripyat Trough; potash horizon; Starobin deposit; saliferous formation; potash ore; rock salt; halopelites